Antioxidant Activity, Vitamin C, and Organoleptic Quality of Flower Kecombrang (Etlinger elatior) Kombucha on Variations of Sugar Types and Fermentation Duration - Novitasari, Hana; Suryani, Titik (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The purpose of this study was to determine the antioxidant activity, vitamin Cand organoleptic quality of torch ginger flower kombucha on variationsof sugar types and fermentation duration. This research method was experiment withCompletely Randomized Design (CRD) with 2 Factors. The first factor was the variations of sugar types (G): palm sugar (200g) and Javanese sugar (200g). The second factor was fermentation duration(F): 5 days and 7 days and green tea kombucha as control. Organoleptic quality testing included color, aroma, taste, and acceptability carried out 20 respondents. The results of the study showed that the highest of the antioxidant activity and vitamin C levels as well as the best organoleptic quality of the torch ginger flower kombucha were 82.54% and 62.65 mg/100 ml as well reddish browncolor, reddish brown color, typical kombucha aroma, sweet and sour taste, and preferred acceptability in the G1F2 treatment (200g palm sugar withfermentation duration of 7 days).